Adipocyte epigenetic alterations and potential therapeutic targets in transgenerationally inherited lean and obese phenotypes following ancestral exposures. (2nd January 2019) - King, Stephanie E.; Nilsson, Eric; Beck, Daniel; Skinner, Michael K.
ABSTRACT: The incidence of obesity has increased dramatically over the past two decades with a prevalence of approximately 40% of the adult population within the United States. The current study examines the potential for transgenerational adipocyte (fat cell) epigenetic alterations. Adipocytes were isolated from the gonadal fat pad of the great-grand offspring F3 generation 1-year old rats ancestrally exposed to DDT (dichlorodiphenyltrichloroethane), atrazine, or vehicle control in order to obtain adipocytes for DNA methylation analysis. Observations indicate that there were differential DNA methylated regions (DMRs) in the adipocytes with the lean or obese phenotypes compared to control normal (non-obese or lean) populations. The comparison of epigenetic alterations indicated that there were substantial overlaps between the different treatment lineage groups for both the lean and obese phenotypes. Novel correlated genes and gene pathways associated with DNA methylation were identified, and may aid in the discovery of potential therapeutic targets for metabolic diseases such as obesity. Observations indicate that ancestral exposures during critical windows of development can induce the epigenetic transgenerational inheritance of DNA methylation changes in adipocytes that ultimately may contribute to an altered metabolic phenotype.